Shrinkage and Cracking Characteristics of Dredged Sludge Containing Straw Fiber Under Different Initial Water Contents - Huiping Qiao; Miaomiao Song; Guizhong Xu; Chengchun Qiu (Buildings)
Dredged sludge usually has high water content and poor engineering properties, which would be unfavorable for its rapid resource utilization. Meanwhile, straw fiber is an environmentally friendly material for improving the mechanical behavior of soil. In this research, a series of shrinkage tests were conducted to investigate the straw fiber effects on the shrinkage behavior of dredged sludge with high water content. Four initial water contents and straw fiber amounts were designed. The water content and crack development were recorded throughout the test. According to the test results, a reduction in water content regarding drying time can be divided into three stages: the constant-rate stage, the falling-rate stage, and the residual stage. At the falling-rate stage, water evaporation is affected significantly by straw fiber. Compared with the sample without straw fiber, the influence of straw fiber on the water evaporation of dredged sludge depends upon the initial water content and the straw fiber content. The straw fiber shows an overall inhibitory effect on the initiation and development of cracks for the tested samples. Moreover, the influence of straw fiber on the shrinkage behavior of dredged sludge depends upon the initial water content and fiber content.